INCEST SEBAGAI BENTUK MANIFESTASI KEKERASAN TERHADAP PEREMPUAN - Dwi Hapsari Retnaningrum (Jurnal Dinamika Hukum, 2009)
Incest is another form of gender-based violence, more specifically a manifestation of violence against women. Categorized as crime under the existing law, there is a strong need not only to suppress this conduct but also to give justice to the victims. At this context, the legal policy to suppress incest can be divided into two main themes. Firstly, is to protect the citizens so that they will not be a victim of incest. Secondly, is to realize the right of victim of incest such as compensation, restitutions et cetera as have been regulated by the law. In addition, this paper recommends non-penal approach to reduce the number of incest.                                                                     Kata kunci : gender-based violence, incest